Chemokine CXCL4 interactions with extracellular matrix proteoglycans mediate widespread immune cell recruitment independent of chemokine receptors - Anna L. Gray; Richard Karlsson; Abigail R.E. Roberts; Amanda J.L. Ridley; Nabina Pun; Bakhtbilland Khan; Craig Lawless; Rafael Luís; Martyna Szpakowska; Andy Chevigné; Catherine E. Hughes; Laura Medina-Ruiz; et al. (Cell Reports, 2023)
Summary: Leukocyte recruitment from the vasculature into tissues is a crucial component of the immune system but is also key to inflammatory disease. Chemokines are central to this process but have yet to be therapeutically targeted during inflammation due to a lack of mechanistic understanding. Specifically, CXCL4 (Platelet Factor 4, PF4) has no established receptor that explains its function. Here, we use biophysical, in vitro, and in vivo techniques to determine the mechanism underlying CXCL4-mediated leukocyte recruitment. We demonstrate that CXCL4 binds to glycosaminoglycan (GAG) sugars on proteoglycans within the endothelial extracellular matrix, resulting in increased adhesion of leukocytes to the vasculature, increased vascular permeability, and non-specific recruitment of a range of leukocytes. Furthermore, GAG sulfation confers selectivity onto chemokine localization. These findings present mechanistic insights into chemokine biology and provide future therapeutic targets.